Understanding the P×S Aspect of Within-Person Variation: A Variance Partitioning Approach - Lakey, Brian (Frontiers in Psychology, 2016)
This article reviews a variance partitioning approach to within-person variation based on Generalizability (G) Theory and the Social Relations Model (SRM). The approach conceptualizes an important part of within-person variation as Person x Situation (PxS) interactions: differences among persons in their profiles of responses across the same situations. The approach provided the first quantitative method for capturing within-person variation and demonstrated very large PxS effects for a wide range of constructs. These include anxiety, five-factor personality traits, perceived social support, leadership, and task performance. Although PxS effects are commonly very large, conceptual and analytic obstacles have thwarted consistent progress. For example, how does one develop a psychological, versus purely statistical, understanding of PxS effects? How does one forecast future behavior when the criterion is a PxS effect? How can understanding PxS effects contribute to psychological theory? This review describes potential solutions to these and other problems developed in the course of conducting research on the PxS aspect of social support. Additional problems that need resolution are identified.